Elementary School Teachers' Perceptions Of Google Meet Training To Address Learning Issues During The Covid-19 Pandemic - Ruswan Dallyono; Farida Hidayati; Diana Anggraeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
The pandemic changed the course of our schools. All traditional face-to-face classes were converted into online classes. This complicates excellent educational planning for practice-based courses, as these courses rely on laboratory facilities to enhance students' abilities. Therefore, social service to 24 elementary school teachers is important through the utilization of online platforms, especially Google Meet. Therefore, the purpose of this paper is to learn about the process of teaching the use of Google Meet during the Covid-19 pandemic, as well as to assess the instructors' opinions on the training and use of this platform. The authors used a qualitative paradigm to describe the learning method and determine instructors' opinions on training using field observations and surveys. Based on documented field observations, course presenters use Google Meet for content discussion. According to this survey, 73.62 percent of the respondents preferred the online learning mode due to the lack of problems encountered. Interestingly, the questionnaire findings revealed 81.95 percent favorable perception of the use of various platforms during the session. This has the potential to be a significant improvement for online courses across all contexts.